A queen mother and the Ottoman imperial harem: Rabia GülnuԞ Emetullah Valide Sultan (1640–1715) - (:unkn) unknown (Oxford University Press, 2017)
The chapter details the life and career of a prominent Ottoman-era concubine and queen mother. It thus contributes to a growing body of scholarship on women in elite Ottoman circles. The period known as the sultanate of women, one in which queen mothers (valide sultans) wielded exceptional authority in social and political circles, lasted roughly from the mid-16th to the mid-17th centuries. A closer look at late 17th-and early 18th-century sources, however, suggests this perception of lessening feminine power does not reflect the historical reality. This chapter challenges the perception of a waning of women’s influence during this period by examining the life and career of Rabia Gülnus Emetullah Valide Sultan (d. 1715). © Oxford University Press 2017. All rights reserved.
Keywords: Concubinage; Court; Gender; Historiography; Islamic history; Ottoman; Slam; Slavery; Women